The dragon and the elephant: Learning from agricultural and rural reforms in China and India - Gulati, Ashok; Fan, Shenggen (International Food Policy Research Institute, 2008)
During the past two-and-a-half decades, China and India have implemented a series of economic reforms that have led to recent growth rates of 9-11 percent per year in China and 8-9 percent per year in India. The rapid economic growth of the two countries has not only captured the attention of the world but has also set into motion a rethinking of the very paradigm of economic development because, despite similar trends in growth rates, the two countries have taken different reform paths, which have led to different rates of poverty reduction. Thus far, agriculture-led growth in China has reduced poverty much faster than has India's experience of liberalizing and reforming the manufacturing sector. With public investments in rural roads and agricultural research and development (R&D) playing critical roles, China has been able to not only feed its population but also raise rural incomes despite having much smaller average landholding size than in India. Nonetheless, there are also lessons to be learned from India's experience. This brief is based on a book, The Dragon and the Elephant: Agricultural and Rural Reforms in China and India (published for IFPRI by Johns Hopkins University Press and, in South Asia, by Oxford University Press-India), which compares the rural development and agricultural reform experiences of China and India and examines the lessons that can be learned from both.